Attenuated clinical and osteoclastic phenotypes of Paget's disease of bone linked to the p.Pro392Leu/SQSTM1 mutation by a rare variant in the DOCK6 gene - Mariam Dessay; Emile Couture; Halim Maaroufi; Frédéric Fournier; Edith Gagnon; Arnaud Droit; Jacques P. Brown; Laëtitia Michou (BMC, 2022)
Abstract Background We identified two families with Paget's disease of bone (PDB) linked to the p.Pro392Leu mutation within the SQSTM1 gene displaying a possible digenism. This study aimed at identifying this second genetic variant cosegregating with the p.Pro392Leu mutation and at characterizing its impact on the clinical and cellular phenotypes of PDB. Methods Whole exome sequencing was performed in one patient per family and two healthy controls. We compared clinical characteristics of PDB in 14 relatives from the two families. The osteoclastic phenotype was compared in in vitro differentiated osteoclasts from 31 participants carrying the DOCK6 and/or SQSTM1 variants. Tridimensional models of SQSTM1 and DOCK6 proteins were generated to evaluate the impact of these variants on their stability and flexibility. Statistical analyses were performed with Graphpad prism. Results Whole-exome sequencing allowed us to identify the p.Val45Ile missense variant in the DOCK6 gene in patients. In both families, the mean age at PDB diagnosis was delayed in pagetic patients carrier of the p.Val45Ile variant alone compared to those carrying the p.Pro392Leu mutation alone (67 vs. 44 years, P = 0.03). Although both p.Val45Ile and p.Pro392Leu variants gave rise to a pagetic phenotype of osteoclast versus healthy controls, the p.Val45Ile variant was found to attenuate the severity of the osteoclastic phenotype of PDB caused by the p.Pro392Leu mutation when both variants were present. The DOCK6 mRNA expression was higher in carriers of the p.Val45Ile variant than in pagetic patients without any mutations and healthy controls. Structural bioinformatics analyses suggested that the p.Pro392Leu mutation might rigidify the UBA domain and thus decrease its possible intramolecular interaction with a novel domain, the serum response factor-transcription factor (SRF-TF)-like domain, whereas the p.Val45Ile variant may decrease SRF-TF-like activity. Conclusion The p.Val45Ile variant may attenuate the severity of the clinical phenotype of PDB in patient carriers of both variants. In vitro, the rare variant of the DOCK6 may have a modifier effect on the p.Pro392Leu mutation, possibly via its effect on the SRF-TF-like.